(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This article examines the structural analysis approach, specifically Vladimir Propp’s methodology as outlined in his book Morphology of the Folktale (1968). Propp analyzed the fundamental narrative elements of fairy tales to identify their core storytelling components. He defined 31 functions that stories follow, with each function representing a recurring element in the narrative sequence. For instance, a common starting point in fairy tales is the initial situation, which Propp labeled as “initial situation”and marked as Function I: “ONE OF THE MEMBERS OF A FAMILY ABSENTS HIMSELF FROM HOME. (Definition: absentation).”